Penggunaan Aplikasi Akuntansi Pada UMKM Kota Demak - Herlinda Yuniar Adyarta; Elen Puspitasari (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Economic growth in a country is progress for that country. In Indonesia itself, one of the factors for economic growth comes from entrepreneurship. These activities are better known as MSMEs. Micro, Small and Medium Enterprises (UMKM) is an activity of business competition in various fields. The purpose of this study was to determine the effect of Business Scale, Company Age, Owner's Education, and Accounting Training have a significant influence on the variable Use of Accounting Applications in MSMEs. The sample is MSMEs in Demak Regency Centra Java. Sampling technique drawed bt using purposive sampling method and obtained 260 MSMEs. This study uses primary obtained by questionaire. Data were analyzed using Multiple Linear Regression Analysis method. The results of this study indicate that Business Scale, Company Age, Owner's Education, and Accounting Training have significant influence on the Use of Accounting Applications in MSMEs.The purpose of this study was to determine the effect of Business Scale, Company Age, Owner's Education, and Accounting Training have a significant effect on the variable Use of Accounting Applications in SMEs. The population in this study is MSMEs in Demak Regency, Central Java. The sampling technique was taken using a purposive sampling method to obtain as many as 260 UMKM. This study uses primary data obtained through questionnaires. Data were analyzed using the Multiple Linear Regression Analysis method. The results of this study indicate that Business Scale, Company Age, Owner's Education, and Accounting Training have a significant effect on the Use of Accounting Applications on UMKM.